IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI KEGIATAN EKSTRAKULIKULER PRAMUKA DI MI MUHAMMADIYAH TEGALURUNG - Muzfirah, Suci; Afdal, Muhammad (Khulasah : Islamic Studies Journal, 2022)
This study aims to describe the implementation of Scout extracurricular activities at MI Muhammadiyah Tegalurung, along with the supporting factors and obstacles. Scout extracurriculars are scheduled once a week after Saturday afternoon. The Scouting education method is carried out classically on the grounds that it is more effective and efficient in terms of time and funding. Even so, MI Muhammadiyah won the top 10 Scout Jamboree for the last. In addition to that, the geographical factor and the distance between the school and the students' homes that are too close to the madrasa are easily seen by Covid-19 officers. Scout extracurriculars are a vehicle for instilling discipline values ​​which are reflected in learning, especially during a pandemic through health protocols, namely wearing masks, washing hands diligently and keeping your distance from teacher supervision. In addition, the activities of Madrasah Ibtidaiyah which are followed by students after learning contribute to forming religious character and noble character. Supporting factors for Scout extracurriculars include teacher human resources and sufficient facilities for training and participating in the Scout Movement Jamboree. The inhibiting factor is the cultivation of values ​​that have not been fully accepted by students. This is overcome by an appreciation approach for the effort obtained by the teacher who is also a Scout coach so that students are enthusiastic about participating in extracurricular activities and build self-confidence